Evaluasi Literasi Teknologi Informasi Disabilitas Netra melalui Implementasi Konten Digital: Studi pada PPSDSN Pendowo Kudus - Muhammad Sholikhan; Irfai Fathurohman; Nur Fajrie (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This study aims to evaluate the improvement of information technology literacy among visually impaired individuals through the implementation of digital content at PPSDSN Pendowo Kudus. The research employed a quantitative approach using a one-group pretest and posttest pre-experimental design, supported by qualitative data. The participants consisted of 10 visually impaired individuals selected through total sampling. The intervention included theoretical instruction on content creation and guided practical sessions in digital content production using audio equipment and digital applications. Data were collected through an information technology literacy questionnaire administered before and after the intervention, as well as semi-structured interviews to obtain supporting qualitative insights. Descriptive analysis showed an increase in the average literacy score from 2.6 to 4.05. The Wilcoxon Signed Rank Test indicated that the difference was statistically significant (p < 0.05). Qualitative findings revealed that the improvement occurred not only in technical skills but also in procedural understanding and confidence in using digital technologies. The findings suggest that digital content implementation designed with attention to accessibility and user experience can serve as an effective strategy to enhance information technology literacy among visually impaired individuals.